2014
DOI: 10.1016/j.foodcont.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-thermal processing technologies on microbial inactivation: An investigation into sub-lethal injury of Escherichia coli and Pseudomonas fluorescens

Abstract: 24In recent years, there has been an increased interest in food processing technologies that 25 could lessen the thermal impact on food products. In the present study, thermosonication 26 (TS) and pulsed electric fields (PEF), applied individually or in combination (TS/PEF), 27were investigated to determine their effects on inactivation and sub-lethal injury of 28Pseudomonas fluorescens and Escherichia coli. TS was applied at a low (L) and high 29 (H) wave amplitude (L; 18.6µm, H; 27.9µm, respectively), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Since these findings, however, obviously are restricted to laboratory conditions, natural occurrence is not documented yet. Nevertheless, the number of studies reporting capability of bacterial populations to build-up tolerance toward novel and mild inactivation treatments has risen the awareness of the scientific community as well as of food business operators in recent years ( Yousef and Courtney, 2003 ; Raso et al, 2005 ; Rajkovic et al, 2010 , 2011 ; Bradley et al, 2012 ; Halpin et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since these findings, however, obviously are restricted to laboratory conditions, natural occurrence is not documented yet. Nevertheless, the number of studies reporting capability of bacterial populations to build-up tolerance toward novel and mild inactivation treatments has risen the awareness of the scientific community as well as of food business operators in recent years ( Yousef and Courtney, 2003 ; Raso et al, 2005 ; Rajkovic et al, 2010 , 2011 ; Bradley et al, 2012 ; Halpin et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, the use of ultrasound allowed a temperature rise of 3.9°C and 2.5°C in the outer and inner portion of sausages, respectively, and could explain at least partially the effect of US on the bacteria. The effect of ultrasound could be also be explained by the evidences that some bacteria were not killed, but sub lethally injured by the application of US leading to weakened cells that are less susceptible to grow (Halpin, Duffy, Cregenzan-Alberti, Lyng, & Noci, 2014;). The more uniform distribution of heating and the increase of the temperature showed by the sausages subjected to the frequency of 25 kHz indicates that it is possible to reduce the pasteurization time, which could lead to lower energy consumption during the process.…”
Section: Microbiological Shelf-life Evaluationmentioning
confidence: 99%
“…Many studies about microbial destruction by microwave treatment have been reported. Halpin et al ( 2014 ) suggested that non-themal treatments for Pseudomonas fluorescens and Escherichia coli had a higher inactivation than that of the thermal treatments. The destruction of microorganisms by microwave at temperatures lower than the thermal destruction point has been observed (Woo et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%